A Simple Cable Radiated Emission Evaluation Method for Table-Top Setups According to CISPR 11 and CISPR 32 - Xinglong Wu; Alessandro Grande; Xiaokang Liu; Flavia Grassi; Giordano Spadacini; Sergio A. Pignari; Fabio Vallarino; Luca Ghezzi (IEEE Access)
CISPR 11 and CISPR 32 define the radiated emission tests to be conducted in a semi-anechoic chamber equipped with controllable turntable and antenna mast, leading to an expensive and time-consuming test procedure. By noting the fact that table-top test setup usually involves long interconnecting cable bundle that radiates significantly, the work proposes a fast and simple pre-compliance radiated emission evaluation method based on cascaded Hertzian dipoles and its radiation theory. Several factors in the CISPR 11/32 test setups are integrated into this evaluation method to mimic a real test procedure. The accuracy of the proposed method is validated by an experimental test. A systematic analysis of the accuracy and applicability of the proposed method is also provided, showing that the method presents a simple, reliable and easy-to-be-implemented prediction tool for early-stage pre-compliance radiation evaluation, according to CISPR 11/32 testing.